A comparative study on financial performance of conventional and Islamic bank: the case of Citibank Berhad and Bank Muamalat Malaysia Berhad / Izianiza Mohd Azmi - Mohd Azmi, Izianiza (Faculty of Business and Management, 2010)
This case study was conducted to evaluate the financial performance of both banks, Citibank Berhad and Bank Muamalat Malaysia Berhad which come from a different banking sector. For completion of this report, secondary data and other approaches such as common sizing, financial ratios and gap analysis has been use as a data collection. The data is taken from external sources such as journal, internet, and newspaper. The study examines five type of ratios include (1) commonsize, (2) liquidity, (3) capital structure and solvency, (4) Return on Investment Result from the financial analysis done provide that Citibank Berhad which is a conventional bank got a strong financial and earned higher profit rather than the Islamic Bank, Bank Muamalat Malaysia Berhad. Separate comparisons of the conventional and Islamic bank for both bank on this case study also showed significant performance different in every ratio category.